Ocena sytuacji finansowej polskich przedsiębiorstw w latach 2002-2003 - Dudycz, Tadeusz; Skoczylas, Wanda; Niemiec, Andrzej (Assessment of the Financial Condition of Polish Enterprises in 2002-2003, 2006)
In the paper the authors present the results of research concerning estimation of financial sis in Polish enterprises between 2002 and 2003. The main results of the analysis show tn enterprises have relatively low profitability with the growing tendency, oversize shoe investments and significant increase of inventory turnover ratio.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 172-190